2021
DOI: 10.34067/kid.0000132021
|View full text |Cite
|
Sign up to set email alerts
|

The Gut and Blood Microbiome in IgA Nephropathy and Healthy Controls

Abstract: Background: IgA nephropathy (IgAN) has been associated with gut dysbiosis, intestinal membrane disruption and translocation of bacteria into blood. Our study aimed to understand the association of gut and blood microbiomes in IgAN patients in relation to healthy controls. Methods: We conducted a case control study with 20 progressive IgAN patients matched with 20 healthy controls, analyzing bacterial DNA quantitatively in blood by 16S PCR and qualitatively in blood and stool by 16S metagenomic sequencing. Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…This has been con rmed in the case of various gastrointestinal and other diseases in which intestinal permeability has been altered [4,42,43]. At the same time, Shah et al later found that the blood microbiome does not directly re ect the gut microbiome [43]. Our study con rms this observation as the beta diversity analysis shows that there is a much larger distance between blood and faecal samples than between blood and skin samples, suggesting that the blood microbiome of healthy individuals may originate from the skin microbiome, which partly coincides with Whittle et al results [6].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This has been con rmed in the case of various gastrointestinal and other diseases in which intestinal permeability has been altered [4,42,43]. At the same time, Shah et al later found that the blood microbiome does not directly re ect the gut microbiome [43]. Our study con rms this observation as the beta diversity analysis shows that there is a much larger distance between blood and faecal samples than between blood and skin samples, suggesting that the blood microbiome of healthy individuals may originate from the skin microbiome, which partly coincides with Whittle et al results [6].…”
Section: Discussionmentioning
confidence: 80%
“…It is considered that microorganisms enter the circulation from different body parts, such as the gut [36]. This has been con rmed in the case of various gastrointestinal and other diseases in which intestinal permeability has been altered [4,42,43]. At the same time, Shah et al later found that the blood microbiome does not directly re ect the gut microbiome [43].…”
Section: Discussionmentioning
confidence: 99%
“…A study on 29 Chinese patients with immunoglobulin A nephropathy (IgAN) also showed a reduced amount of Clostridia, Eubacterium, and Alistipes compared with healthy controls, indicating the pathogenic role of depletion of SCFA-producing bacteria in systemic inflammation and IgAN progression [53]. In patients with IgAN, a higher abundance of class Coriobacteriia and genera Legionella, Enhydrobacter, and Parabacteroides was present in the blood, and genera Bacteroides, Escherichia-Shigella, and Ruminococcus in stool in comparison with healthy controls [51]. Additionally, a clinical study in ESKD patients identified six taxa, including Akkermansia, Dialester, Enterococcus, Rominicoccus, Blautia, and Bacteroides, that contributed to the elevated levels of uraemic toxins [57].…”
Section: Human Studiesmentioning
confidence: 99%
“…In comparison with healthy controls patients with IgAN had higher proportions of the species of the genera Bacteroides, Escherichia-Shigella, and some Ruminococcus. 72 Another study that analyzed fecal gut microbiota in 52 Chinese patients with IgAN and 25 healthy controls found abundance of Bacteroides compared to healthy controls. 73 The study also highlighted that gut microbial modifications may be associated with the clinical severity of IgAN, pointing that patients with higher urine red blood cell counts or proteinuria levels had a higher percentage of Escherichia-Shigella and a lower percentage of Bifidobacterium.…”
Section: Gut Microbiota and Iganmentioning
confidence: 99%